3-Methyladenine can depress drug efflux transporters via blocking the PI3K–AKT–mTOR pathway thus sensitizing MDR cancer to chemotherapy. (November 2014) - Zou, Zhenyou; Zhang, Jing; Zhang, Haiyang; Liu, Huan; Li, Zhiguo; Cheng, Dan; Chen, Jun; Liu, Lu; Ni, Mengjie; Zhang, Yu; Yao, Jun; Zhou, Jun; et al.
Abstract Multi-drug resistance (MDR) cancer is an intractable problem. Over-expression of drug efflux transporters such as ABCB1, ABCC1 and ABCG2 contributes to it, by which they pump drugs out of cells, and result in the decrease in the efficacy of chemotherapy. To reverse the cancer MDR, we used 3-methyladenine (3-MA) treatment on taxol or doxorubicin stressed MDR cell lines A2780DX5 and SGC7091R and xeno-tumor implanted mice. The results indicate that ABCB1, ABCC1 and ABCG2 were depressed, and the PI3K–AKT–mTOR pathway was blocked. Moreover, using FITC-labeled taxol as the indicator, we observed that the drug accumulation was enhanced in MDR cells and more cells were killed after 3-MA administration. Thus suggesting that 3-MA can reverse cancer MDR via depressing agent-efflux transporters.